Професійна культура фахівця як соціально-професійний феномен - Марченко, О. Г.; Marchenko, O. H.; Ольга Марченко (Інноваційна педагогіка. - 2023. - Вип. 58, т. 1. - С. 161-165, 2023)
У статті обґрунтована доцільність розгляду професійної культури фахівця як соціально-професійного феномену. Загальна культура особистості проявляється в догляді за собою, покращенні, ушляхетненні тілесно-душевно-духовних нахилів та здібностей і проявляється в культурі тіла, душі, духовній культурі. З’ясовано, що професійна культура інтегрується до загальної культури особистості. До соціально-спрямованого компоненту професійної культури належать аксіосфера особистості, взаємне проникнення професійно-корпоративних і загальнолюдських гуманістичних цінностей, що є основою професійної етики фахівця, запорукою збереження високоморального обличчя в повсякденній практиці. Виокремлені такі соціально-орієнтовані складові професійної культури, як критичне мислення, ефективна комунікація, емоційний інтелект, соціальний інтелект, здатність вирішувати проблеми, знаходити можливості та ресурси для цього, допитливість, ділова хватка. Професійно-орієнтовані елементи визначаються профілем підготовки фахівця.

The article substantiates the feasibility of considering the professional culture of a specialist as a socio-professional phenomenon. The general culture of the individual is manifested in self-care, improvement, ennoblement of physical, mental and spiritual inclinations and abilities and is manifested in the culture of the body, soul, and spiritual culture. It was found that the professional culture is integrated into the general culture of the individual. The socially-directed component of professional culture includes the axiosphere of the individual, the mutual penetration of professionalcorporate and universal humanistic values, which is the basis of professional ethics of a specialist, the guarantee of maintaining a high moral face in everyday practice. Such sociallyoriented components of professional culture as critical thinking, effective communication, emotional intelligence, social intelligence, ability to solve problems, find opportunities and resources for this, curiosity, business acumen is singled out. Professionally oriented elements are determined by the profile of specialist’s training. Clarification of the essence of the studied concepts was carried out from the positions of phenomenological, cultural, competence, axiological, professional-oriented, resource-based, system-synergistic methodological approaches. The theoretical basis of the study of the problem of the formation of the professional cultural of a specialist is the law on the dependence of the content and intensity of the formation of the professional culture of a specialist on the economic, socio-political, scientific and technical training opportunities, dependence of the level of professional culture on the level of professional preparation of a specialist. The prerequisites for the formation of the professional culture of a specialist are the satisfaction of basic personal needs, professional self-determination, self-actulization, the creation of psychоlogical and pedagogical conditions under which a student of higher education can take active subject position, facilitation as the implementation of an important function of a teacher, which consists in encouraging students of higher education to critically perception of information and its creative processing, feedback in the process of evaluating the student’s learning results, creation of a favorable emotional and psychоlogical climate.

В статье обоснована целесообразность рассмотрения профессиональной культуры специалиста как социально-профессионального феномена. Общая культура личности проявляется в уходе за собой, улучшении, облагораживании телесно-душевно-духовных наклонностей и способностей и проявляется в культуре тела, души, духовной культуре. Выяснено, что профессиональная культура интегрируется в общую культуру личности. К социально-направленному компоненту профессиональной культуры относятся аксиосфера личности, взаимное проникновение профессионально-корпоративных и общечеловеческих гуманистических ценностей, являющихся основой профессиональной этики специалиста, залогом сохранения высоконравственного лица в повседневной практике. Выделены такие социально-ориентированные составляющие профессиональной культуры, как критическое мышление, эффективная коммуникация, эмоциональный интеллект, социальный интеллект, способность решать проблемы, находить возможности и ресурсы для этого, любознательность, деловая хватка. Профессионально ориентированные элементы определяются профилем подготовки специалиста.
Professional culture as a social-professional phenomenon
Keywords: професійна освіта; professional education; профессиональное образование; професійна культура; professional culture; профессиональная культура; професійна підготовка фахівця; professional training of a specialist; профессиональная подготовка специалиста; культура; culture